2006
DOI: 10.1002/cb.185
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between product involvement and consumer decision‐making styles

Abstract: Recently, a number of studies have investigated consumer decision‐making styles (CDMS) and their importance to consumer behaviour research. However, research designs suggested to date are mainly replications of a study by Sproles and Kendall (1986) proposing eight mental characteristics, the so‐called Consumer Styles Inventory (CSI). The CSI has been applied across cultures, but without critically examining its validity and reliability. A major concern is the postulated product independence of CSI. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 33 publications
(28 reference statements)
4
108
0
14
Order By: Relevance
“…The concept of self-gift giving has been linked to impulse buying, even though there is a lack of empirical research on the relationship between the two concepts (Silvera et al, 2008). Product involvement refers to a consumer's long-term attachment to a specific object and has a significant impact on his or her decision-making process (Bauer et al, 2006). Academic literature on the topic has been relatively scarce (Ward and Tran, 2008;Heath et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of self-gift giving has been linked to impulse buying, even though there is a lack of empirical research on the relationship between the two concepts (Silvera et al, 2008). Product involvement refers to a consumer's long-term attachment to a specific object and has a significant impact on his or her decision-making process (Bauer et al, 2006). Academic literature on the topic has been relatively scarce (Ward and Tran, 2008;Heath et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Manu studies were mostly tested product neutral setting and still there is lack of research on consumer decision making styles with respect to food product environment. Many researchers recognized that a consumer may have different styles for each food product category (Bauer 2006). All this supports there is need for research on food related consumer decision making styles.…”
Section: India's Background -Economic Changes and The Retail Environmentmentioning
confidence: 99%
“…Product involvement studies measuring different products have found varying levels of involvement based on the types of consumer goods analyzed (e.g., instant coffee versus cameras) (Bauer, Sauer, & Becker, 2006;McQuarrie & Munson, 1992;Zaichkowsky, 1985). A connection between product involvement and purchase intentions was hypothesized in the present study.…”
Section: What Is the Effect Of Innovation Type On The Dissemination Omentioning
confidence: 68%
“…Attitudinal items derived from a twelve-item scale developed by Bauer et al (2006). Their study examined an individual's attitudinal product involvement with consumer products hypothesized to have high involvement (stereo system, jeans, watch) and low involvement (toothpaste, chocolate bar, yogurt).…”
Section: Product Involvementmentioning
confidence: 99%
See 1 more Smart Citation